Construction Methods Commonly Used For Affordable Housing in Malaysia - Lee, Chung Ee; Zeinab, Ahmadi Danesh (2016)
Despite the Malaysian government recent urge to provide adequate housing for different income group, there is no significant research on constructing technologies used in affordable housing. Furthermore, the quality of the affordable housing provided does not satisfy the user's expectation [1].Hence, this paper aims to examine the various construction technologies used in affordable housing in Malaysia. Affordable housing is further divided to low-income housing and housing targeted for middle-income groups.A quantitative approach was taken and a questionnaire was distributed to developers and contractors and overall 36 response was collected. The findings reveal that different contractors and developers decide the construction methods based on their experience and preference and the client's requirements. However, based on the respondents experience Flat’s are the most appropriate type of housing for low-income group, whereas for middle-income group terrace houses are considered suitable. As for the construction method used; regardless of the type of housing , Concrete is commonly used for building frame and precast concrete is widely used for the external walls.